PD-1 inhibition plus platinum-based chemotherapy (PBC) or PBC alone in the first-line treatment of locally advanced or metastatic pulmonary lymphoepithelioma-like carcinoma - Zhang, Xuanye; Zhou, Yixin; Chen, Hualin; Chen, Chen; Lin, Zuan; He, Li-na; Du, Wei; Chen, Tao; Hong, Shaodong; Fu, Sha (Frontiers in Immunology, 2022)
Background Pulmonary lymphoepithelioma-like carcinoma (PLELC) is a distinctive subtype of non-small cell lung carcinoma that was not well presented in clinical studies. The management of advanced PLELC remains an important, unmet need due to the paucity of high-grade evidence. Herein, we carried out a multicenter, retrospective study to assess the effectiveness and tolerability of PD-1/PD-L1 inhibitor plus chemotherapy versus chemotherapy alone for patients with advanced PLELC in the first-line setting. Patients and Methods This retrospective study enrolled patients with advanced PLELC receiving first-line treatment with PD-1 inhibition plus chemotherapy (IO-Chemo group) or chemotherapy alone (Chemo group) in three medical centers in China. The survival outcomes, efficacy, and safety profile were investigated. The primary endpoint was progression-free survival (PFS). Secondary endpoints included objective response rate (ORR), overall survival (OS), and adverse events (AEs). Results A total of 133 patients were enrolled. PFS was significantly longer in the IO-Chemo group (median 12.8 months [95% CI 5.2-20.4]) than that in the Chemo group (median 7.7 months [95% CI 6.8-8.6]; hazard ratio [HR] 0.48 [95% CI 0.31-0.74]; P=0.001). ORR was 74.5% (95% CI, 63.0-86.1) in the IO-Chemo group and 34.6% (95% CI, 24.1-45.2) in the Chemo group (P<0.001). The median OS was not reached in the IO-Chemo group versus 35.7 months (95% CI 26.7-44.8) in the Chemo group (HR 0.47 [95% CI 0.20-1.07]; P=0.065). Multivariate analysis revealed that PD-1/PD-L1 inhibitor combination was independently associated with longer PFS (HR 0.40 [95% CI 0.25-0.63]; P<0.001). Grade 3 or higher AEs occurred in 36 (65.5%) patients in the IO-Chemo group and 56 (71.8%) patients in the Chemo group, respectively. Conclusions In patients with advanced PLELC, adding PD-1/PD-L1 inhibitor to platinum-based chemotherapy significantly increased PFS and ORR with a tolerable safety profile.